SIKAP DAN KEPUASAN KONSUMEN DALAM MENGONSUMSI JAMU KUNYIT ASAM INSTAN SEBAGAI MINUMAN KESEHATAN DI KOTA BANDAR LAMPUNG - Shofy Aulia Afifah; Yaktiworo Indriani; Wuryaningsih Dwi Sayekti (Lampung University, 2024)
The purposes of this study were to analyze the decision-making process and consumer attitudes, to observe consumption patterns and to measure the level of consumer satisfaction of Sido Muncul and Herbadrink instant sour turmeric herbs in Bandar Lampung City. This study used the survey method and was conducted in January-February 2023 in Bandar Lampung by distributing the Google Form questionnaires. The number of respondents in this study was 80 people. The data were analyzed by descriptive analysis, Fishbein's multiattributes and Customer Satisfaction Index (CSI). The results showed that consumers consumed instant tamarind turmeric herbal medicine in order to relieve menstrual pain. All consumers were satisfied and agreed to repeat purchases. If the product runs out where consumers tend to buy, consumers would buy elsewhere. Measurement of consumers attitudes toward multi-atribute products resulted Ao score of 89.179 (Sido Muncul) and 86.688 (Herbadrink). The average amount of consumption of Sido Muncul herbal medicine was higher. Both consumers liked the original variant and made purchases every month before menstruation. The level of consumer satisfaction for both brands of herbal medicine was included in the satisfied category in which CSI scores of Sido Muncul sour turmeric was 79.95 and Herbadrink was 79.10.Key words: attitudes, consumers, jamu, satisfaction